LATEST ADVANCEMENTS AND APPLICATIONS OF LASERS IN THE FIELD OF PROSTHODONTICS: A REVIEW (Journal of Pharmaceutical Negative Results, 2022)
Laser is no more new entity in the field of dentistry. Mostly lasers therapies are related to the improvement of facial esthetics however, intraoral uses are also imperative. Laser therapies are also advised for minor oral surgical procedures with minimum bleeding. Lasers in prosthodontics may also be used in fixed or removable prosthesis, implantology and in case of maxillofacial rehabilitation. In fixed Prosthodontics, lasers are mostly used for crown lengthening and associated soft tissue management. In oral implantology, lasers are primarily advised for implant site making, associated gingival modifications and other nearby soft tissues management. In removable Prosthodontics, lasers are highly recommended in certain pre-prosthetic surgeries before planning actual prosthesis. Pre prosthetic surgeries performed by lasers usually exhibit clear operatory field and optimal access due to less bleeding and trauma. Therefore considering all these imperative points in mind, this article was planned to discuss the latest advancements and applications of lasers in the field of prosthodontics.